Plasma exchange as a rescue therapy for treatment-resistant thyroid storm with concurrent heart failure: a literature review based on a case report - Pouya Ebrahimi; Moloud Payab; Maryam Taheri; Salma Sefidbakht; Neda Alipour; Taha Hasanpour; Pedram Ramezani; Mahbube Ebrahimpur; Hamid Reza Aghaei Meybodi (International Journal of Emergency Medicine)
Abstract Introduction Thyroid storm or severe hyperthyroidism can present with various signs and symptoms. They are mostly controlled by general treatment, such as anti-thyroid drugs and other medications to control clinical features. However, in rare cases, they are more severe, and they only respond to more aggressive treatments, such as plasmapheresis and total thyroidectomy. The final histopathological features, such as the loci of differentiated thyroid carcinoma, are sometimes surprising. Case presentation Here, we present a 40-year-old female who presented with severe palpitation, diaphoresis, and chest pain. After taking the initial steps of treatment and stabilizing the patient, the history, physical exam, and laboratory results confirmed the diagnosis of a thyroid storm in the background of Graves’ disease that is accompanied by heart failure with reduced ejection fraction (HFrEF). She was admitted to an ICU setting and received principal treatment of thyroid storm. However, the systematic treatment was not effective, and finally, plasmapheresis and total thyroidectomy were performed. Histopathologic evaluation following surgery confirmed the presence of foci of papillary thyroid carcinoma (PTC) in the background of the grave’s disease. This case underscores the complexity of managing Grave’s induced thyroid storm in severe cases, which might lead to plasmapheresis and total thyroidectomy. Urgent and invasive treatment may be necessary in rare cases when normally applied treatment modalities are not able to control the situation and result in life-threatening critical health conditions. In such a severe case, it can result in serious cardiovascular complications such as decompensated heart failure with a high rate of mortality. Key clinical message Thyroid storm, though rare, can be accompanied by severe medical conditions such as heart failure and death. In cases in which primary medical and symptomatic therapies do not work, more aggressive treatment (such as plasmapheresis and total thyroidectomy) should be considered. On the other hand, precise histopathologic evaluation of the thyroid tissue is necessary.